SEKTOR EKONOMI DALAM KEGIATAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN - Yuli Rahmini Suci; Ahok Alpa Beta (Universitas Muhammadiyah Jambi, 2017)
The economic sector is always changing following macro growth. The influence of competition among companies in attracting consumers is unlikely to be avoided. BAROKAH Store is one of the trading companies that are trying to increase sales by increasing promotion to attract consumers to stay and sales increase.